LEGAL ANALYSIS ON THE LAW OF THE BOY BERNARDO AND ITS EFFECTIVENESS IN PRACTICAL APPLICATIONS (CIPEEX, 2022)
THE MENINO BERNARDO LAW, LAW NO. 13.010, OF JUNE 26, 2014, WAS CREATED TOGUARANTEE CHILDREN AND ADOLESCENTS THE RIGHT TO BE RAISED AND EDUCATED WITHOUT THE USE OFPUNISHMENT (PHYSICAL PUNISHMENT AND/OR CRUEL OR DEGRADING TREATMENT). LAW NO. 13.010/2014CAME TO MEET THE DEVICE ART. 227 OF THE FEDERAL CONSTITUTION WHERE IT IS EXPLICIT THAT IT IS THEDUTY OF THE FAMILY, SOCIETY AND THE STATE TO ENSURE WITH ABSOLUTE PRIORITY TO CHILDREN, ADOLESCENTSAND YOUNG PEOPLE SEVERAL RIGHTS, INCLUDING DIGNITY AND RESPECT (FEDERAL CONSTITUTION OF 1988).IN THIS SENSE, THIS PAPER AIMS TO UNDERSTAND WHAT IS BEING DONE TO MAKE THIS LAW EFFECTIVE ANDWHAT PUBLIC POLICIES ARE BEING IMPLEMENTED TO ENSURE THESE RIGHTS. WITH THE CREATION OF THEMENINO BERNARDO LAW, THE NEED WAS FELT TO CREATE POLICIES TO TRAIN THE PROFESSIONALS WHODIRECTLY ASSIST THIS PUBLIC TO PREVENT, IDENTIFY, AND COMBAT THESE FORMS OF VIOLENCE. THE FEDERALGOVERNMENT HAS CREATED TRAINING PROGRAMS, ESPECIALLY FOR GUARDIANSHIP COUNSELORS WHO DEALDIRECTLY WITH MOST OF THE CHILD AND ADOLESCENT VICTIMS OF ABUSE. BESIDES THESE ACTIONS, BRAZIL ISPART OF A GLOBAL PARTNERSHIP FOR THE END OF VIOLENCE AGAINST CHILDREN LED BY THE UN (WHERE THEGOAL IS TO CONTRIBUTE TO THE ELIMINATION OF ALL FORMS OF VIOLENCE AGAINST CHILDREN ANDADOLESCENTS). WHAT MEASURES ARE TAKEN FOR THOSE RESPONSIBLE WHO, INSTEAD OF CARING,EDUCATING AND PROTECTING THESE VULNERABLE MINORS, USE PHYSICAL PUNISHMENT, CRUEL ORDEGRADING TREATMENT? THEY WILL BE SUBJECT TO FAMILY PROTECTION PROGRAMS, PSYCHOLOGICAL ORPSYCHIATRIC TREATMENT, ORIENTATION PROGRAM COURSES, THE OBLIGATION TO REFER THE CHILD TOSPECIALIZED TREATMENT AND/OR A WARNING. IN PRACTICE, PERMANENT EDUCATIONAL CAMPAIGNS SHOULDBE PROMOTED, INVOLVING THE JUDICIARY, THE PUBLIC MINISTRY AND THE GUARDIANSHIP COUNCIL TOPROMOTE THE PROTECTION AND DEFENSE OF THE RIGHTS OF CHILDREN AND ADOLESCENTS. IT IS UNDENIABLETHAT THE CHILD BERNARDO LAW WAS A MILESTONE IN THE FIGHT AGAINST THE EXCESSES AND ABUSES THATCULTURALLY ARE CARRIED OUT AS IF IT WERE NORMAL, BUT IT IS STILL ONLY THE BEGINNING OF THIS FIGHT. EVENTHOUGH THESE CHANGES HAVE BROUGHT COUNTLESS BENEFITS, WE STILL NEED TO CONTINUE FIGHTINGAGAINST THE INEQUALITIES AND EVILS EXERCISED MAINLY BY THOSE WHO SHOULD PROTECT, WELCOME, ANDGUIDE IN AN ADEQUATE MANNER.
Keywords: child and adolescent law; maltreatment; public policy